The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s12197-008-9051-5
|View full text |Cite
|
Sign up to set email alerts
|

The Feldstein–Horioka puzzle in Latin American and Caribbean countries: a panel cointegration analysis

Abstract: Panel Unit Root, Cross Section Dependence, Panel Cointegration, Capital Mobility, C23, F2, F4,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…The average investment over GDP is 18. Murthy (2008). 19. International Monetary Fund, World Economic Outlook (WEO) database, April 2015.…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The average investment over GDP is 18. Murthy (2008). 19. International Monetary Fund, World Economic Outlook (WEO) database, April 2015.…”
Section: Methodology and Datamentioning
confidence: 99%
“…9. See, for example, Kim, Oh, and Jeong (2005); Bahmani-Oskooee and Chakrabarti (2005); Murthy (2008); Kumar and Rao (2011).…”
mentioning
confidence: 99%
“…Some studies analyzing East-Asian and African countries have revealed low saving-retention coefficient, contradicting the Feldstein-Horioka puzzle (Narayan, 2005;Guillaumin, 2009;Wang, 2013;Raheem, 2017;Murthy & Ketenci, 2021), while other papers have found little evidence on increased capital flows (Kim et al, 2007;Mitra, 2017;Kaur & Sarin, 2018;Patra & Mohanty, 2020;Yilanci & Kilci, 2021). A limited number of studies focusing on the degree of international capital mobility in the region of Latin America and the Caribbean have demonstrated low saving-retention coefficient, an indicator of high capital mobility (Murthy, 2009;Rocha, 2009;Kumar, 2015;Cavallo & Pedemonte, 2016); however, the studies either analyse a limited sample of Latina American and Caribbean countries or employ outdated panel estimation techniques or as in case of Kumar (2015) focus only on one of the Latina American regional integration agreements (MERCOSUR). Thus, this paper contributes to the literature on the Feldstein-Horioka puzzle by analysing the extent of capital flows from both regional and global perspective in three Latin American and Caribbean regional trade agreements: SICA, Andean Community and MERCOSUR.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author finds evidence of an intermediate degree of capital mobility. Murthy (2009) assesses the degree of capital mobility in 19 Latin American and Caribbean countries over the period 1960-2002, employing the Pedroni panel Group FMOLS technique. Similar to Rocha (2009), the author confirms a moderate degree of capital IJOEM 19,4 mobility.…”
Section: Capital Mobilitymentioning
confidence: 99%
“…The authors find that saving and investment series are cointegrated; however, the results are interpreted in terms of capital mobility rather than current account sustainability, which contradict the solvency constraint theory. Furthermore, Murthy (2009) and Cavallo and Pedemonte (2016) utilize the Pedroni panel group FMOLS estimator, which has limited power in the presence of cross-sectional dependence. Moreover, none of the existing studies have analyzed the degree of capital mobility in the SICA and the Andean community.…”
Section: Capital Mobilitymentioning
confidence: 99%